Development of Innovative Creative Character instruments for students in Denpasar - Devi Rahmawati; Nyoman Dantes; Ni Ketut Suarni (Bisma The Journal of Counseling, 2021)
The purpose of this study is to develop and test the feasibility of innovative creative instruments, so as to produce valid and reliable data in measuring innovative creative characters. The innovative creative character instrument is a measuring tool for counseling teachers to determine the level of innovative creative character in students. This study uses themethod Research and Development. Based on the validity test using the product moment formula and reliability using the Cronbach alpha formula, this innovative creative character instrument that has been developed has met the validity and reliaility criteria which can be classified as high. It can be concluded that the development of creative and innovative character instruments for high school/vocational high school students meets the validity standard for measuring innovative creative characters in high school/vocational high school students.